2019
DOI: 10.1038/s41598-019-46501-4
|View full text |Cite
|
Sign up to set email alerts
|

Microbial and abiotic controls on mineral-associated organic matter in soil profiles along an ecosystem gradient

Abstract: Formation of mineral-organic associations is a key process in the global carbon cycle. Recent concepts propose litter quality-controlled microbial assimilation and direct sorption processes as main factors in transferring carbon from plant litter into mineral-organic associations. We explored the pathways of the formation of mineral-associated organic matter (MOM) in soil profiles along a 120-ky ecosystem gradient that developed under humid climate from the retreating Franz Josef Glacier in New Zealand. We det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(64 citation statements)
references
References 51 publications
3
60
1
Order By: Relevance
“…On average 1.46 ± 0.67 % of the fresh litter layer C was associated with minerals in the topsoil, 0.57 ± 0.12 % in the upper subsoil, and only 0.01 ± 0.02 % in deeper subsoil compartments 22 months after adding the labeled beech litter, emphasizing the subordinate importance of recent aboveground litter inputs to soil C stocks in all depths, especially the deeper subsoil. Also Lajtha et al (2014a) showed that 50 yrs of doubled litter inputs in a deciduous forest stand did not result in a net accumulation of OC in the topsoil HF, likely as sorption sites in topsoils are already largely occupied by OM (Mikutta et al, 2019). The element composition on the mineral surfaces of the HF supports this assumption, as the C and N contents decreased on the mineral surfaces with increasing soil depth (Supplement, Fig.…”
Section: Mineral-associated Om and Incorporation Of Litter-derived C mentioning
confidence: 74%
See 1 more Smart Citation
“…On average 1.46 ± 0.67 % of the fresh litter layer C was associated with minerals in the topsoil, 0.57 ± 0.12 % in the upper subsoil, and only 0.01 ± 0.02 % in deeper subsoil compartments 22 months after adding the labeled beech litter, emphasizing the subordinate importance of recent aboveground litter inputs to soil C stocks in all depths, especially the deeper subsoil. Also Lajtha et al (2014a) showed that 50 yrs of doubled litter inputs in a deciduous forest stand did not result in a net accumulation of OC in the topsoil HF, likely as sorption sites in topsoils are already largely occupied by OM (Mikutta et al, 2019). The element composition on the mineral surfaces of the HF supports this assumption, as the C and N contents decreased on the mineral surfaces with increasing soil depth (Supplement, Fig.…”
Section: Mineral-associated Om and Incorporation Of Litter-derived C mentioning
confidence: 74%
“…Beside bioturbation and rhizodeposition, translocation and sorption of DOM to the soil matrix are the other prominent processes transferring C to the subsoil (Kaiser and Kalbitz, 2012;Mikutta et al, 2019). The observed strong decrease in the contents of mineral-associated OC with soil depth (Fig.…”
Section: Mineral-associated Om and Incorporation Of Litter-derived C mentioning
confidence: 93%
“…The lack of correlation between simulated soil C : N and litter C : N in MIMICS-CN simulations suggests an intriguing followup question: in the field, is SOM stoichiometry correlated with litter quality, or is it better explained by climate, edaphic, and mineralogical gradients that impact soil microbial community composition, microbial activity, and mineral-mediated mechanisms of SOM persistence? Various regional studies provide limited support for the relationships generated by MIMICS-CN between soil C : N and MAT (Miller et al, 2004) or clay content (Hassink et al, 1993;Homann et al, 2007;Jenny, 1941), though a largescale synthesis of measurements across all of these variables is still needed. Presently, MIMICS-CN assumes that microbial biomass stoichiometry largely controls the C : N ratios of stable SOM, with relatively minor contributions from litter quality.…”
Section: Exploring Emergent Som Dynamicsmentioning
confidence: 99%
“…However, a small proportion of litter inputs become stabilized in MIMICS-CN without first passing through the stoichiometric filter of microbial biomass, and increasing this fraction in the model is a means to increase the C : N of simulated stable SOM. The strength of the mineral sink for microbial necromass in the model also impacts the relative balance of microbe-or plant-derived stable SOM, which in turn impacts modeled soil C : N. This result implies that in the field, C : N stoichiometry might be used as a means to differentiate the degree to which a given soil fraction is derived from direct plant inputs or microbial biomass, and mineralogical variables might be useful for explaining differences in fraction distributions across soils that impact C : N. Studies like Mikutta et al (2019) illustrate the way that C : N can be used to assess the relative contributions of plant matter or microbial residues to stable SOM. Future work will use measured C : N of soils and soil fractions and isotopic insights into the plant or microbial origins of stable SOM to improve the parameterization of this aspect of the model and better understand the relationship between mechanisms of SOM stabilization and soil stoichiometry.…”
Section: Exploring Emergent Som Dynamicsmentioning
confidence: 99%
“…Predicting the stoichiometry of MAOM thus requires an understanding of which compounds are adsorbed onto mineral surfaces under what conditions. The quantity, stability, chemistry, and distribution of MAOM in an ecosystem is determined by the relative dominance of biotic vs. abiotic pathways to sorption, whether DOM is adsorbed directly to mineral surfaces or after it is processed by soil microbes (Mikutta et al, 2019;. Because microbes tend to outcompete minerals for organic matter (Fischer et al, 2010), the biotic pathway increases in prevalence with microbial biomass such that sorption of microbiallyprocessed compounds dominates in surface soil horizons and rhizosphere soils .…”
Section: Stabilization Of Mineral-associated Organic Mattermentioning
confidence: 99%